Multi-scale order in amorphous transparent oxide thin films - Yan, A; Sun, T; Borisenko, K; Buchholz, D; Chang, R; Kirkland, A; Dravid, V (2012)
Nominally diffraction amorphous materials represent a pervasive challenge in establishing classical structure-property relationships. This stems from the difficulty in defining the structure of nominally amorphous materials and experimentally differentiating the short-range (10 Å) and medium-range (10 to 30 Å) order as a function of process parameters which are important due to their influence on physical, chemical, or transport properties. Herein, we report on the determination of short- and medium-range order in nominally amorphous zinc and tin co-substituted indium oxide In 1.4Zn 0.3Sn 0.3O 3 (a-ZITO) thin films grown by pulsed laser deposition. These thin films are being explored as transparent conductors that exhibit changes in transport properties depending on deposition temperature while remaining diffraction amorphous. Reduced density function (RDF) analysis from electron diffraction accompanied by density functional theory molecular dynamics simulation of a liquid quench suggests ordering at short range. Scanning transmission fluctuation electron microscopy (STFEM) indicates the presence of ordered ZITO regions at medium range. For a-ZITO films grown at different temperatures, RDF analysis showed no significant change in the short range order. However, STFEM revealed notable structural (and symmetry) differences at medium range. The existence of this type of multi-scale local order in amorphous ZITO thin films highlights the importance of a combined approach to unravel the structures of nominally amorphous materials and to understand structure-properties correlations. © 2012 American Institute of Physics.